Evolution of the phase stability of Ni-Al under low energy ball milling - Zelaya, Maria Eugenia (2013)
Low energy mechanical alloying of Ni–35 at.%Al and Ni–40 at.%Al material was performed and the resulting structures were investigated by XRD and TEM. The final intermetallics observed consist of two phases, NiAl(B2) and Ni3Al while 7R and 3R martensite was observed in post-annealed samples. Different integrated milling times were associated to the intermetallic consolidation and initial blend dissociation.